Conceptual modelling of residents' environmental sanitation behaviour in a Nigerian metropolis - Oluwole Daramola (Economic and Environmental Studies (E&ES), 2016)
This study modelled residents' environmental sanitation behaviour in Ibadan metropolis, Nigeria. To examine the factors influencing environmental sanitation behaviour, residents were sampled across the residential areas of the metropolis. The identified factors were residents' socioeconomic background, residential characteristics, access to environmental sanitation facilities and services, and agreement with environmental sanitation exercise. Findings revealed that environmental sanitation exercise was a strong and statistically significant predictor (R2 = .971) of environmental sanitation behaviour in Ibadan metropolis while other factors were trailing behind with 2.9% contribution. These findings suggest that environmental sanitation in Ibadan metropolis was mainly an exercise rather than a practice. It was law-driven, and therefore mostly government-initiated and motivated. These findings have implications for practice and policy making by highlighting environmental sanitation reorientation and strengthening of other identified factors of environmental sanitation behaviour in the metropolis.
Keywords: D19; K32; 330; environmental behaviour; environmental sanitation; Ibadan metropolis; model; Nigeria; residents